Incentives in prescribing, dispensing and pharmaceutical spending: A scientometric mapping. [version 2; peer review: 2 approved] - Riascos-Ochoa J; Tocaruncho-Ariza L. H; Jimenez-Barbosa W. G (F1000Research)
Introduction Health systems worldwide are struggling to ensure the affordability of medicines. Prescription, dispensing, and pharmaceutical expenditures are key variables that highlight the need to understand how global scientific evidence is generated against factors (implicit and non-explicit) that influence these variables. Objectives Explore and provide a detailed description of the characteristics of the global scientific production of Open Access articles related to the prescription, dispensing and pharmaceutical expenditure faced by health systems worldwide. Methods A five-stage scientometric mapping was performed based on a systematic search of 8 databases. The five stages are: i) retrieval, ii) migration, iii) analysis, iv) visualization and v) interpretation. Results A corpus of evidence from 103 systematic literature reviews was obtained, screened and sifted, visualizing the countries, authors, databases, journals, institutions and time periods that contributed most to evidence generation. Central research themes are identified and phenomena related to article publication are discussed. Conclusions The analysis reveals a clear leadership of the United Kingdom and the United States in scientific production on prescribing, dispensing and pharmaceutical expenditure in health systems worldwide. This scientific production is mainly focused on financing policies, pharmaceutical incentives and interventions, and rational use of medicines. There is also evidence of the scarcity of scientific production in Latin American publications and authors, which could generate interest for future research.